Koresh ebook The true story of david koresh and the tragedy at waco. - Talty, Stephan (2023)
"Impressively researched and written with storytelling verve. ... Talty delves the deepest into the history and twisted personality of David Koresh ." —Wall Street Journal The first comprehensive account of David Koresh's life, his road to Waco, and the rise of government mistrust in America, from a master of narrative nonfiction No other event in the last fifty years is shrouded in myth like the 1993 siege of the Branch Davidians in Waco, Texas. Today, we remember this moment for the 76 people, including 20 children, who died in the fire; for its inspiration of the Oklahoma City bombing; and for the wave of anti-government militarism that followed. What we understand far less is what motivated the Davidians' enigmatic leader, David Koresh. Drawing on first-time, exclusive interviews with Koresh's family and survivors of the siege, bestselling author Stephan Talty paints a psychological portrait of this infamous icon of the 1990s. Born Vernon Howell into the hyper-masculine world of central Texas in the 1960s, Koresh experienced a childhood riven with abuse and isolation. He found a new version of himself in the halls of his local church, and love in the fundamentalist sect of the Branch Davidians. Later, with a new name and professed prophetic powers, Koresh ushered in a new era for the Davidians that prized his own sexual conquest as much as his followers' faith. As one survivor has said, "What better way for a worthless child to feel worth than to become God?" In his signature immersive storytelling, Talty reveals how Koresh's fixation on holy war, which would deliver the Davidians to their reward and confirm himself as Christ, collided with his paranoid obsession with firearms to destructive effect. Their deadly, 51-day standoff with the embattled FBI and ATF, he shows, embodied an anti-government ethic that continues to resonate today. Now, thirty years after that unforgettable moment, Koresh presents the tragedy at Waco—and the government mistrust it inspired—in its fullest context yet.